Why and How to Switch to Genomic Selection: Lessons From Plant and Animal Breeding Experience - , R2D2 Consortium; Fugeray-Scarbel, Aline; Bastien, Catherine; Dupont-Nivet, Mathilde; Lemarié, Stéphane (Frontiers in Genetics, 2021)
The present study is a transversal analysis of the interest in genomic selection for plant and animal species. It focuses on the arguments that may convince breeders to switch to genomic selection. The arguments are classified into three different “bricks”. The first brick considers the addition of genotyping to improve the accuracy of the prediction of breeding values. The second consists of saving costs and/or shortening the breeding cycle by replacing all or a portion of the phenotyping effort with genotyping. The third concerns population management to improve the choice of parents to either optimize crossbreeding or maintain genetic diversity. We analyse the relevance of these different bricks for a wide range of animal and plant species and sought to explain the differences between species according to their biological specificities and the organization of breeding programmes.